Pull-off force modeling and experimental study of PDMS stamp considering preload in micro transfer printing. (1st June 2020) - Liang, Cunman; Wang, Fujun; Huo, Zhichen; Shi, Beichao; Tian, Yanling; Zhao, Xingyu; Zhang, Dawei
Abstract: Micro transfer printing is an effective method for heterogeneous materials integration in soft micro device fabrication. In micro transfer printing, controllable adhesion force is an important and desired feature. In this paper, an accurate theoretical pull-off force model is established considering the influence of not only the pull-off velocity but also the preload in micro transfer printing, which reveals the relationships between the pull-off force and the pull-off velocity as well as preload. Experimental tests are carried out to investigate the influences of both pull-off velocity and preload on pull-off force and validate the theoretical model. The results show that the proposed pull-off force model matches well with the experiment data. The pull-off force of the stamp increases approximately linearly with the preload and the preload under large pull-off velocity has a greater influence on the pull-off force than that under small pull-off velocity. Therefore, the analytic model can not only provide an important understanding of micro transfer printing, but also support important information for the process optimization of micro transfer printing. Graphical abstract: Image, graphical abstract